(3GdJThjb Edi ML GdHjJ GdYJjbs - (3eMH GdOjf CMeO Hf YHO Gddg Hf CHj HcQ GdWHQj GdTGaYj, CHh LYaQs ((3eMeO Hf YKeGf Hf YHO GdQMef Hf YjSi Hf ehSi GdeQGcTi s)
(3ChdgG (B:s
(3CeG HYO agPG cJGH CThb ajg Edi GdML hEdi CKGQg hCHjf ETGQGJg hCcTa Yf CSQGQg hSejJg HcJGH GdJThjb Edi ML GdHjJ GdYJjb s
(3BNQgG (B:s
(3SeYJ eMeO eNdO jbhd bOeJ ef GdML fLR GdcJGH HMeO Gddg s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B410s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdTGaYjs